2007
DOI: 10.1063/1.2784384
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the complexity of excised larynx vibrations from high-speed imaging using spatiotemporal and nonlinear dynamic analyses

Abstract: In this paper, we investigate the biomechanical applications of spatiotemporal analysis and nonlinear dynamic analysis to quantitatively describe regular and irregular vibrations of twelve excised larynges from high-speed image recordings. Regular vibrations show simple spatial symmetry, temporal periodicity, and discrete frequency spectra, while irregular vibrations show complex spatiotemporal plots, aperiodic time series, and broadband spectra. Furthermore, the global entropy and correlation length from spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 30 publications
0
32
0
2
Order By: Relevance
“…This laryngeal pathology may cause biomechanical changes in the viscoelastic properties of the vocal folds. Canine larynges represent an adequate organ model of human phonatory structures [3,6,7]. In the work reported in this Letter, an excised canine larynx is used to produce the pathological condition of a vocal fold scar.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This laryngeal pathology may cause biomechanical changes in the viscoelastic properties of the vocal folds. Canine larynges represent an adequate organ model of human phonatory structures [3,6,7]. In the work reported in this Letter, an excised canine larynx is used to produce the pathological condition of a vocal fold scar.…”
mentioning
confidence: 99%
“…1b shows nine successive image frames of a scarred larynx. The glottal edges were obtained using the image edge detection method [6,7]. A reference line from the anterior to the posterior ends of the vocal folds was determined.…”
mentioning
confidence: 99%
“…28 Rich irregular vibratory behaviors, such as bifurcation and chaos, can be found in a voice production system. 4,5,[29][30][31][32][33][34] Some studies have investigated the generation of nonlinear dynamic properties in voice. It has been found that irregular vibratory patterns are related to left-right asymmetry of the vocal folds.…”
Section: Chaotic Vibrationmentioning
confidence: 99%
“…In addition, excised larynx approaches allow the straightforward collection of data that are either challenging or impossible to obtain using human and animal in vivo set-ups, such as the measurement of glottal source parameters without the influence of the vocal tract, the measurement of vocal fold impact stress, and the examination of vocal fold vibration from an inferior or medial (i.e., using a hemilarynx) observation position. Recent work in this area has focused on medial surface dynamics during vocal fold vibration (Döllinger & Berry, 2006a, non-linear pressure-flow and pressure-frequency relationships (Alipour & Jaiswal, in press;Alipour & Scherer, 2007), non-linear vibratory patterns present at high P s (Jiang, Zhang, & Ford, 2003;Jiang, Zhang, & Stern, 2001;Zhang, Jiang, Tao, Bieging, & MacCallum, 2007), flow velocity fields and flow vortices (Khosla, Murugappan, Gutmark, & Scherer, 2007;Khosla, Murugappan, Lakhamraju, & Gutmark, 2008), and the influence of supraglottic anatomy on phonation (Alipour, Jaiswal, & Finnegan, 2007;Döllinger, Berry, & Montequin, 2006;Finnegan & Alipour, in press). …”
Section: Excised Larynx Phonationmentioning
confidence: 99%